Automatic mold sheet moving-out device, use method and application - ZHAN XIANFENG; ZHOU HUAJIN (2016)
The invention discloses an automatic mold sheet moving-out device, a use method and application. A mold sheet sucking mechanism comprises a plurality of suction cups, pipelines, an installation base, guide sleeves and guide sleeve bases, wherein the suction cups are connected to the installation base and are connected to a pressure distribution mechanism through the pipelines, the guide sleeve bases are arranged on the top of the installation base, and the guide sleeves are arranged on the guide sleeve bases in an interference mode. A mold sheet moving mechanism comprises guide columns, guide column fixing bases and an air cylinder, wherein the guide columns are fixed to the guide column fixing bases and are arranged in the guide sleeves in a sleeved mode, the guide column fixing bases are connected to external fixing mechanisms, and the moving end of the air cylinder is connected to the installation base. According to the automatic mold sheet moving-out device, mold sheets can be moved out from equipment fast, and the defect can be avoided. The mold sheets tend to deform when taken out manually because the exerted force is often excessively great. According to the automatic mold sheet moving-out device, the mold sheets can be moved out from the equipment uniformly through the suction cups, and deformation can be avoided; the production efficiency of the mold sheets is improved, and the manpower is saved.